Theoretical study of the possibility of glycin with thiotriazoline complexes formation - L. I. Kucherenko; O. V. Khromyleva; I. A. Mazur; S. V. Shishkina (Zaporožskij Medicinskij Žurnal)
Brain strokes are widely spread all over the world and are among the most dangerous for the population. Often it leads to death, complete or partial loss of ability to work. The correction of imbalance of Excitatory and inhibitory neurotransmitter systems by activation of natural inhibitory processes is a promising direction of primary neuroprotection in cerebral ischemia. Particular attention is drawn to the natural inhibitory neurotransmitter – glycine and its role in the mechanisms of acute cerebral ischemia. There are data on the ability of the thiotriazoline antioxidant to potentiate the therapeutic effect of neurometabolic cerebroprotectors. Therefore, the creation of new combined preparation based on glycine with thiotriazoline is important today.